178k views
5 votes
What is the solution to the equation 3x + 2(x − 9) = 8x + x − 14? (5 points)

User JSK
by
5.6k points

2 Answers

4 votes

Answer:

x = -1

Explanation:

3x+2(x-9)=8x+x-14 ;; equation

simplify the equation to the form

3x+2(x-9)=8x+x-14

reorder the terms in parentheses

3x+(+2x-18)=8x+x-14

remove unnecessary parentheses

+3x+2x-18=+8x+x-14

move all terms containing x to the left and all other terms to the right.

+3x+2x-8x-1x=-14+18

simplify left and right side of the equation.

-4x=+4

divide both sides of the equation by -4 to get x.

x=-1

User Alpha Hydrae
by
4.8k points
3 votes

Answer:

x= -1

Explanation:

User Dmitriy Tarasevich
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.